Comparative study of worm‐like chain models for collagen molecules. Issue 1 (17th December 2018) - Hillgärtner, Markus; Linka, Kevin; Itskov, Mikhail
Abstract: Collagen is the main structural protein in various biological tissues and of high interest for microstructural multi‐scale models due to its load bearing functionality. The worm‐like chain (WLC) model [4] with its approximation [6] is a widely used approach for the modeling of DNA, which has a helical structure similar to tropocollagen. However, the classical WLC is suitable only for the entropic deformation regime of collagen. By modeling the extension behavior, it fails to give accurate predictions when the helical structure of the molecule starts twisting under higher loads. The twistable worm‐like chain [3] and its special case referred to as the extensible worm‐like chain [7] aim to include the mechanical coupling between bond stretching and twist of the helix using a twist‐stretch coupling term, leading to more accurate predictions in the energetic regime. This contribution discusses different variations and coupling terms describing the molecular behavior behind the transition state between the entropic and energetic regime. Experimental data of the literature [1] are used to make a quantitative comparison of the discussed models and their applicability.